2021
DOI: 10.2147/ndt.s296986
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Insomnia with Depression and Anxiety Symptoms in Patients Undergoing Noncardiac Surgery

Abstract: Objective Insomnia is common in patients undergoing surgery. It can increase the rate of postoperative complications, interfere with patient recovery, and decrease hospital satisfaction. However, there are few studies on perioperative insomnia. This study was conducted to investigate the differences in the demographic, health status, and clinical characteristics of patients with and without insomnia postoperatively, and to identify the potential risk factors of insomnia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Numerous studies have demonstrated that preoperative anxiety and depression adversely affect sleep quality both before and after surgery. Higher levels of psychological distress correlate with poorer sleep quality during the perioperative period, leading to a higher incidence of PSD (Du et al, 2023; Gu et al, 2023; Huang et al, 2021; Mansano-Schlosser et al, 2017; S. J.Wang et al, 2022; Z.Wang et al, 2023; Wright et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that preoperative anxiety and depression adversely affect sleep quality both before and after surgery. Higher levels of psychological distress correlate with poorer sleep quality during the perioperative period, leading to a higher incidence of PSD (Du et al, 2023; Gu et al, 2023; Huang et al, 2021; Mansano-Schlosser et al, 2017; S. J.Wang et al, 2022; Z.Wang et al, 2023; Wright et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Carr et al [3] reported a 67% incidence of perioperative anxiety in patients undergoing gynecologic laparoscopy. Perioperative anxiety is associated with higher postoperative pain, greater opioid use, and an increased risk of adverse postoperative outcomes, which is detrimental to patients' postoperative recovery [4,5]. Therefore, methods to reduce perioperative anxiety and facilitate patients' postoperative recovery are receiving increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders severely impact the quality of life of patients and are risk factors for secondary diseases such as diabetes [4,5], cardiovascular diseases [6,7], depression [8], and thyroid diseases [9]. Additionally, sleep disorders can be caused by various diseases [10][11][12]. The incidence of insomnia in the United States is approximately 10-22% [13,14].…”
Section: Introductionmentioning
confidence: 99%